2013
DOI: 10.1177/1403494813510792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol and other drugs and the concentrations in blood of drivers killed in road traffic crashes in Sweden

Abstract: The high median BAC in fatally-injured drivers speaks strongly towards alcohol-induced impairment as being responsible for the crash. Compared with alcohol, the prevalence of illicit and psychoactive prescription drugs was fairly low despite a dramatic increase in the number of drug-impaired drivers arrested by the police after a zero-tolerance law was introduced in 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
14
2
4
Order By: Relevance
“…The percentage of cannabis positive cases in this study is higher than the 3% reported in Sweden (as THC) [17], 7% reported in France (as THC) [11] and 9.8% reported in the USA (analyte not stated) [25]. But lower than the 27% reported in Canada (as THC and/or carboxy-THC) [1] and 30% reported in New Zealand (as THC) [13].…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…The percentage of cannabis positive cases in this study is higher than the 3% reported in Sweden (as THC) [17], 7% reported in France (as THC) [11] and 9.8% reported in the USA (analyte not stated) [25]. But lower than the 27% reported in Canada (as THC and/or carboxy-THC) [1] and 30% reported in New Zealand (as THC) [13].…”
Section: Resultscontrasting
confidence: 76%
“…This is lower than all of the similar studies reported in the literature, including the 21% in Sweden (limit = 20 mg/100 mL) [17], 11% in France (limit = 50 mg/100 mL) [11], 25% in Norway (limit = 20 mg/100 mL) [14], 36% in Brazil (zero tolerance) [8], and 29% in Australia (limit = 50 mg/100 mL) [7]. Of the alcohol-positive drivers, 75%…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…A positive blood sample is required to prosecute a driver suspected of DUID. Samples are sent to a national accredited laboratory at the National Board of Forensic Medicine in Linköping where the toxicological analyses are performed according to accredited standardized screening and verification procedures to determine the presence and concentrations of alcohol and illicit as well as prescription drugs that may affect driving ability (Jones, 2005;Ahlner et al, 2014). These include amphetamines, cannabis, ecstasy, opioids (opiates as well as synthetic and semi-synthetic opioids), cocaine and benzodiazepines, although the verification analyses depends on the specific substance or substances present at screening (i.e.…”
Section: Drug-impaired Driving In Swedenmentioning
confidence: 99%
“…O uso múltiplo de drogas, por si só, já tem sido identificado como agravante para o acontecimento de comportamentos de risco ou acidentes no contexto do trânsito, inclusive com o acometimento de vítimas de morte 38,39,40 . Estudo retrospectivo conduzido na Suécia 40 avaliou as concentrações de álcool e de outras drogas em 895 amostras de sangue de motoristas que morreram em acidentes de trânsito, tendo sido identificado que 1,8% deles haviam consumido álcool e alguma droga ilícita; 3,5%, álcool e algum medicamento prescrito; e, finalmente, 0,9% havia consumido álcool + droga ilícita + medicamento.…”
Section: Discussionunclassified